2019
DOI: 10.2196/14705
|View full text |Cite
|
Sign up to set email alerts
|

Acupuncture to Improve Symptoms for Stable Angina: Protocol for a Randomized Controlled Trial

Abstract: Background Acupuncture has demonstrated physiologic analgesic effects in Chinese patients with stable angina. One proposed mechanism of action for these analgesic effects is the downregulation of M1 macrophages, interleukin 1 beta, interleukin-6, interleukin-18, and tumor necrosis factor alpha. Objective This study aims to test a 10-session, 5-week acupuncture treatment protocol as a complementary therapy for symptoms of stable angina for American patie… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 46 publications
0
6
0
Order By: Relevance
“…The quality of these outcomes was low and very low, thus, we could not come to a firm conclusion. Acupuncture has physiologic analgesic effects [41], and our study indicated that acupuncture on DAM could effectively improve SAP. Nevertheless, the mechanisms have not yet comprehensively explained.…”
Section: Discussionmentioning
confidence: 60%
“…The quality of these outcomes was low and very low, thus, we could not come to a firm conclusion. Acupuncture has physiologic analgesic effects [41], and our study indicated that acupuncture on DAM could effectively improve SAP. Nevertheless, the mechanisms have not yet comprehensively explained.…”
Section: Discussionmentioning
confidence: 60%
“…We are currently pilot testing a standardized acupuncture prescription (Figure 1), similar to the protocol of Zhao et al, 9 in a diverse sample of Americans in our Acupuncture to Improve Symptoms for Angina (AIMS-A) study. 10…”
Section: Acupuncture For Stable Anginamentioning
confidence: 99%
“…Nonetheless, in assessing the effects of acupuncture, undoubtedly, the major and yet unsolved problem is the placebo effect. 4,5 Even with the sham group, such a placebo effect cannot be ruled out; however, it may occur more frequently in patients who undergo the standard medical therapy alone. The study by Yang et al 5 involved patients who underwent the standard medical therapy.…”
mentioning
confidence: 99%
“…2 Among such non-pharmacological treatments for angina pectoris, interest in acupuncture seems to be increasing recently, due to its efficacy. [4][5][6] Therefore, we focus on acupuncture as an additional treatment procedure for angina pectoris.…”
mentioning
confidence: 99%
See 1 more Smart Citation